2012
DOI: 10.1016/b978-0-444-59426-6.00007-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon optogenetics

Abstract: The use of optogenetics, the technology that combines genetic and optical methods to monitor and control the activity of specific cell populations, is now widely adopted in neuroscience. The development of optogenetic tools, such as natural photosensitive ion channels and pumps or calcium- and voltage-sensitive proteins, has been growing tremendously during the past 10 years, thanks to the improvement of their performances in terms of facilitating light stimulation. To this aim, efficient illumination methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 77 publications
1
94
0
Order By: Relevance
“…Many optogenetic applications require manipulating select cells within a population with high spatiotemporal precision. Two-photon digital holography (2P-DH) is an effective method to flexibly target light to many regions simultaneously, or to produce an extended image to excite large patches of membrane for summation of single-channel ionic currents (13). It was recently shown that 2P scanning excitation of MAG 2p could depolarize neurons, but scans of nearly 1 s were necessary (32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many optogenetic applications require manipulating select cells within a population with high spatiotemporal precision. Two-photon digital holography (2P-DH) is an effective method to flexibly target light to many regions simultaneously, or to produce an extended image to excite large patches of membrane for summation of single-channel ionic currents (13). It was recently shown that 2P scanning excitation of MAG 2p could depolarize neurons, but scans of nearly 1 s were necessary (32).…”
Section: Resultsmentioning
confidence: 99%
“…Using digital holography (2P-DH) (13,34), we demonstrate that activation of L-MAG0 460 is compatible with functional imaging using the red genetically encoded calcium indicator R-GECO1.0 (35). This combination of optical tools facilitates fast, multicellular stimulation and recording, an important benchmark for the utility of PTLs for in vivo optogenetic studies.…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…For instance, cellular resolution functional imaging will require novel 2p microscopes that are able to monitor activity patterns of a large number of neurons updated at approximately each millisecond. The current trend of 2p optical instrumentation advances toward solutions that involve spatial, temporal, and possibly spectral multiplexing strategies enabled by multifocal, temporal focusing and holographic technologies (Emiliani et al 2015;Oron et al 2012;Shtrahman et al 2015). Another possibility that should not be neglected is 1p approaches that resolve single cells in vivo such as GRIN lenses (Jung et al 2004;Tang et al 2015) or light sheet approaches (Bouchard et al 2015).…”
Section: Systems-level Voltage Imaging Approachesmentioning
confidence: 99%
“…[29][30][31] Both for optogenetics and uncaging, the light should ideally be delivered to the specimen in a way that allows targeting single excitable units, which can be specific parts of a tissue, single cells, or even subcellular compartments, such as neuronal dendrites or spines. [32][33][34] In the case of dendritic spine observation, this is all the more important since it has been shown that dendritic spines exhibit collective *Address all correspondence to: Valentina Emiliani, E-mail: valentina.emiliani@ parisdescartes.fr behaviors even when separated by several microns. 35,36 Also, nonlinear synaptic integration along dendrites has been found.…”
Section: Introductionmentioning
confidence: 99%